2009
DOI: 10.1155/2009/369129
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Epigenetic Inactivation of hMLH1 and BRCA1 in Tunisian Patients with Invasive Breast Carcinoma

Abstract: Aberrant hypermethylation of gene promoter regions is one of the mechanisms for inactivation of tumour suppressor genes in many human cancers including breast carcinoma. In the current study, we aimed to assess by MSP, the methylation pattern of two cancer-related genes involved in DNA repair: hMLH1 (mutL homolog 1, colon cancer, nonpolyposis type 2 (E. coli) and BRCA1 (breast cancer 1, early onset) in 78 primary breast cancers from Tunisian patients. The methylation frequencies were 24.36% for hMLH1 and 46% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
(39 reference statements)
2
17
0
Order By: Relevance
“…However, Xu X et al (29) on the basis of a large population-based study demonstrated decreased survival associated with BRCA1 promoter methylation among women with BC. Similar were the findings of Karray-Chouayekh S et al (28) and Chen Y et al (23). The better survival rate found here by the Kaplan-Meier method was supported by a protective, though not statistically significant, effect of BRCA1 hypermethylation as revealed by the univariate Cox proportional hazards model.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, Xu X et al (29) on the basis of a large population-based study demonstrated decreased survival associated with BRCA1 promoter methylation among women with BC. Similar were the findings of Karray-Chouayekh S et al (28) and Chen Y et al (23). The better survival rate found here by the Kaplan-Meier method was supported by a protective, though not statistically significant, effect of BRCA1 hypermethylation as revealed by the univariate Cox proportional hazards model.…”
Section: Discussionsupporting
confidence: 91%
“…Heterogeneity is observed both with respect to frequency and clinical correlations. The reported frequency of BRCA1 promoter hypermethylation in sporadic breast carcinomas is in the range of 9 to 59% (15,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The frequency found here is the first reported in Bulgarian patients with BC and is a little below the average BRCA1 hypermethylation frequency.…”
Section: Discussionmentioning
confidence: 43%
“…Together, our results suggest that regulation of BRCA1 by hypoxia occurs through at least two mechanisms: activation of the E2F/p130 pathway to mediate acute downregulation (1) and induction of repressive histone modifications, especially H3K4 demethylation by LSD1, as a step toward epigenetic silencing (2). Silencing of BRCA1 has previously been associated with promoter DNA hypermethylation at CpG islands, based on observations in human tumor specimens (8,14,21,35,50). However, we could not detect any cytosine methylation either at the endogenous BRCA1 promoter in MCF-7 cells after hypoxia exposure or at hypoxia-induced, silenced BRCA1 promoters in BSH8-derived cells.…”
Section: Discussionmentioning
confidence: 60%
“…20 These primers amplify a 182-bp product. 20,21 The PCR was carried out in a 25 μL mixture containing 10 mM tris hydrochloride (pH, 8.3), 50 mM potassium chloride, 1.5 mM magnesium chloride, 5 units of recombinant Taq DNA polymerase, 200 µM of dNTP, 0.6 µM of each primer, and 2.5 µL of bisulfate-treated template DNA.…”
Section: Methylation-specific Pcrmentioning
confidence: 99%